Peningkatan Efikasi Vaksinasi pada Ikan Nila (Oreochromis niloticus) dengan Penambahan Ekstrak Tanaman Terung Asam dan Lempuyang - Hardi, Esti Handayani; Sukarti, Komsanah; Anggridini, Maulina (Jurnal Veteriner, 2020)
This research was aimed to evaluate the Solanum ferox/SF and bitter ginger (Zingiber zerumbet/ZZ) in increasing the effectiveness of the Pseudomonas sp. (EP-02) vaccine through immersion in tilapia (Oreochromis niloticus).  The dose used was 600 mg.L-1 of SF; 200 mg.L-1 of ZZ and vaccine bacterial density used 108 CFU.mL-1, the ratio between vaccine and extract was 1: 1: 1.  The test were begun with immersion the tilapia in the vaccine and extract for 20 minutes, the challenges test was done on day 7th (d7), 14th  (d14) and 21th (d21) post-vaccination with the combined bacteria Aeromonas hydrophila (EA-01) and Pseudomonas fluorescens (EP-01) (concentration of each bacteria was 105 CFU.mL-1) through intramuscular injection of 0.1 mL each fish.  Abnormal swimming patterns, pathology of anatomy, total mortality, survival rate, RPS, were measured at week 2 after the challenge test. Application of SF and ZZ extracts in vaccination can increase the non specific (haematology parameters) and specific immunity (phagocytic index and antibody) since d7 of vaccination. While the increasing fish immunity in vaccine groups occurred in d14 post vaccination.  The extract administration in vaccination reduced the fish mortality; increased SR and RPS of tilapia faster than the vaccination group. In conclusion, addition of SF and ZZ extracts can increase the efficacy of vaccines faster and more effectively from day 7th of infection.